FIBRO-LEIOMYOMA OF CERVIX SIMULATING CERVICO-VAGINAL PROLAPSE AND ITS MANAGEMENT IN A CROSSBRED COW - A CASE REPORT - Hadiya, KK; Parikh, PV; Parmar, KH; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The incidence of pedunculated tumors in the bovine genital system is rare; while as cervical tumors are still rarer. Jubb and Kennedy (1970) and Roberts (1971) described fibromas, fibrosarcomas, leiomyomas and carcinomas affecting bovine cervix and vagina. Cervical and/or vaginal tumors simulating and/or causing cervico-vaginal prolapse have been documented as a cause of infertility in cows and buffaloes by Derashri et al. (1985), Kochhar et al. (1996) and Ryot (2000). Further, Sharma et al. (1977) and Kochhar et al. (1995) described tumors of cervix & vagina in buffaloes. Such rare pedunculated cervical tumors have also been reported in a pregnant Rathi cow (Kohli and Bishnoi, 1980), a lactating crossbred cow (Sindhaye, 1982) and an infertile cow (Ryot, 2000). The present report places on record a case of pedunculated large cervical fibro-leiomyoma and its successful treatment by surgical intervention in a crossbred cow.